PARTICIPATION OF INSTITUTIONAL INVESTORS IN THE CAPITAL MARKET: IN THE CASE OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
This article focuses on the current situation, participants and problematic aspects of the national capital market in the study of some issues in the activity of institutional investors in the capital market of our country. Based on the analysis, appropriate conclusions and proposals are formed.